Star Wars psychology : : dark side of the mind - Goldman, Carrie; Langley, Travis,( 1964-) (New York, NY :: Sterling New York, 2015)
Offers a fascinating psychological analysis of the compelling and complex universe of George Lucas's richly rendered Star Wars series. A group of expert contributors examines such topics as family ties, Jedi qualities, masculinity, girl power, and the values embodied in both the "dark" and "light" sides of this psychologically spellbinding world.
"This book is an independent publication and not associated with or authorized, licensed, or endorsed by any person or entity affiliated with the well-known Star Wars movies, publications, or TV shows"--Cover.
Includes bibliographical references and index.
Keywords: Star Wars films -- Psychological aspects; Psychology; Motion pictures -- Psychological aspects; Motion pictures -- Psychological aspects; Good and evil; Sex role -- Psychological aspects; Families -- Psychological aspects; Heroes in motion pictures; Psychology; Popular works